A Comprehensive Monte Carlo Model of the Grafting of Maleic Anhydride onto Polypropylene with Experimental Validation - Romero Pietrafesa, Tomás (2023)
A Monte Carlo model is employed to investigate the grafting of maleic anhydride onto polypropylene using a peroxide initiator. The study aimed to develop a comprehensive model that considered a very detailed kinetic mechanism, including chain transfer to polymer, homopolymerization as well as several copolymer reactions. The relative importance of these reactions is evaluated using a sensitivity analysis, which identified homopolymerization, β-scission, chain grafting, and termination by disproportionation as the most influential reactions. The kinetic constants of these reactions are tuned to fit reported experimental data using the Surface Response Method. The model considers a pseudo-homogeneous reaction medium and predicts average molecular weights, degree of grafting, molecular weight distribution, and grafting distribution. Furthermore, model simulations provided useful information about the impact of initial concentrations of reactants and reaction time on the molecular properties of the grafted polymer.